Swallowing in behavioral variant frontotemporal dementia - MARIN, Sheilla de Medeiros Correia; MANSUR, Letícia Lessa; OLIVEIRA, Fabricio Ferreira de; MARIN, Luis Fabiano; WAJMAN, José Roberto; BAHIA, Valéria Santoro; BERTOLUCCI, Paulo Henrique Ferreira (Arquivos de Neuro-Psiquiatria, 2021)
Background: Swallowing and feeding problems may occur with the progression of behavioral variant frontotemporal dementia (bvFTD) and can impair the anticipatory and oral preparatory phases of swallowing. Objective: To characterize swallowing problems and the feeding situation of patients with bvFTD and to correlate the swallowing problems with functionality, executive functions, cognitive and behavioral features. Methods: Consecutive outpatients with bvFTD in mild, moderate and severe dementia stages were recruited along with their caregivers. Patients and caregivers were screened with the following scales: “Mini-Mental State Examination”, “Severe Mini-Mental State Examination”, “FTLD-modified Clinical Dementia Rating”, “Neuropsychiatric Inventory”, “Frontal Assessment Battery”, “Index of Independence in Activities of Daily Living”, “Swallowing Rating Scale” and “Assessment of Feeding and Swallowing Difficulties in Dementia”. Results: Overall, thirty patients with bvFTD were included along with their caregivers. Patients with bvFTD showed feeding and swallowing difficulties such as: messy to eat, passivity, coughing and choking, difficulty with some food consistencies and with specific food. Swallowing problems in bvFTD correlated with impaired functionality (p<0.05) and cognition (p<0.05), executive dysfunction (p<0.01) and behavioral features (p<0.01). Caregivers had great difficulty in managing the feeding situation during mealtime, with different characteristics in each dementia stage. Conclusion: Patients with bvFTD had inappropriate speed eating, passivity, coughing and choking starting in the mild dementia stage, and these problems worsen in the severe stage. Such difficulties affected caregiver performance during mealtime. The correlations indicated that swallowing difficulties tend to follow cognitive and behavioral decline in patients with bvFTD.
Keywords: Frontotemporal Dementia; Deglutition Disorders; Feeding Behavior; International Classification of Functioning, Disability and Health; Cognition Disorders